2004
DOI: 10.1042/bj20040226
|View full text |Cite
|
Sign up to set email alerts
|

Protein interaction quantified in vivo by spectrally resolved fluorescence resonance energy transfer

Abstract: We describe a fluorescence resonance energy transfer (FRET)-based method for finding in living cells the fraction of a protein population (alpha(T)) forming complexes, and the average number (n) of those protein molecules in each complex. The method relies both on sensitized acceptor emission and on donor de-quenching (by photobleaching of the acceptor molecules), coupled with full spectral analysis of the differential fluorescence signature, in order to quantify the donor/acceptor energy transfer. The approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 50 publications
3
118
0
Order By: Relevance
“…The direct excitation of acceptors was even lower, however, as the efficiency of excitation at 458 nm is only 9% of that at 514 nm (i.e. max for YFP) (37). For cells expressing low levels of acceptor relative to donor, it is likely that most of the acceptor-tagged receptors are in donor-containing complexes and undergo FRET; moreover, the likelihood of such complexes increases with the size of the oligomer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct excitation of acceptors was even lower, however, as the efficiency of excitation at 458 nm is only 9% of that at 514 nm (i.e. max for YFP) (37). For cells expressing low levels of acceptor relative to donor, it is likely that most of the acceptor-tagged receptors are in donor-containing complexes and undergo FRET; moreover, the likelihood of such complexes increases with the size of the oligomer.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance of the donor (a D ) was obtained from Equation 19, in which Q D is the quantum yield of eGFP taken as 0.64 (37). Equation 19 incorporates a correction for the FRET efficiency as determined by donor dequenching (1 Ϫ E app ddq ) and for the difference between excitation at 458 nm and excitation at 488 nm (e D 458 ).…”
Section: Estimation Of [A] T /[D] T -Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because receptor dimers versus oligomers could not be distinguished by simple FRET experiments used to show that ␣-factor receptors interact, other approaches have been required to address this question. Among such methods, quantitative FRET imaging and donor dequenching upon acceptor photobleaching have been applied recently to coexpressed CFP-and YFP-tagged ␣-factor receptors (86). Remarkably, these studies showed that in the absence of agonist, the entire ␣-factor receptor population on the plasma membrane or the endoplasmic reticulum (ER) apparently is, on average, dimeric.…”
Section: ␣-Factor Receptor Oligomers Versus Dimers: Does Size Matter?mentioning
confidence: 99%
“…Analytical methods have been used to detect and characterize microdomains in membranes, [11][12][13] monitor lipid and protein interactions, 14,15 and to investigate proteins that form oligomeric complexes. [16][17][18][19] One of the advantages of analytical expressions is that they uniquely describe the FRET efficiency for a specific fluorophore distribution. Yet, this advantage also becomes a limitation as these models often show poor transferability to other systems.…”
Section: Introductionmentioning
confidence: 99%